A highly selective fluorescent sensor for Al3+ and the use of the resulting complex as a secondary sensor for PPi in aqueous media: its applicability in live cell imaging1. Issue 25 (7th July 2015) - Liang, Chunshuang; Bu, Wenhuan; Li, Chenglong; Men, Guangwen; Deng, Mengyu; Jiangyao, Yukun; Sun, Hongchen; Jiang, Shimei
<x xml:space="preserve">Abstract</x> An "off–on–off" reversible fluorescent sensor has been developed for sequential detection of Al3+ and PPi in aqueous media, and has further been applied to live cell imaging.